Prinsip Effectivites Penentuan Kedaulatan atas Pulau dalam ICJ Judgment on Land and Maritime Delimitation and Sovereignty over Islands (Gabon/Equatorial Guinea) - Basri, Muhammad Aswar; Furqon, Arimbi Fajari (Soedirman Law Review, 2025)
Disputes concerning sovereignty over territory frequently arise before the International Court of Justice (ICJ), often involving diverse forms and historical backgrounds. In the context of sovereignty disputes over islands, the ICJ has applied the principle of effectivités as a significant factual criterion in determining sovereignty. This principle was notably applied in the case of Land and Maritime Delimitation and Sovereignty Over Islands (Gabon/Equatorial Guinea), decided by the Court on 19 May 2025. The dispute concerned Equatorial Guinea’s claim over several small islands adjacent to Gabon. Against this background, this article examines: (1) the concept and legal status of the principle of effectivités in international law, and (2) its application in the aforementioned case. From a normative legal perspective, this article identifies and explains the principle of effectivités as a basis for determining sovereignty over the disputed islands. In international law, the principle requires that a state demonstrate effective control and administration over a territory and its population in order to be recognized as sovereign. In the case at hand, the Court considered that Equatorial Guinea had undertaken measures indicative of occupation of the islands. These measures included political actions, such as issuing a decree and communicating it to the UN Secretary-General in 1970 without objection, as well as technical acts. It must be tangibly manifested, for instance, through the construction of infrastructure, thereby demonstrating a state’s commitment to maintaining sovereignty. Such practice may serve as a useful reference for Indonesia, as an archipelagic state, in safeguarding its own territorial sovereignty.